Recruiting Ethnically Diverse General Internal Medicine Patients for a Telephone Survey on Physician-Patient Communication - Nápoles-Springer, Anna M (Blackwell Science Inc, 2005)
BACKGROUND: Limited evidence exists on the effectiveness of recruitment methods among diverse populations. OBKECTIVE: Describe response rates by recruitment stage, ethnic-language group, and type of initial contact letter (for African-American and Latino patients). DESIGN: Tracking of response status by recruitment stage and ethnic-language group and a randomized trial of ethnically tailored initial letters nested within a cross-sectional telephone survey on physician-patient communication. PARTICIPANTS: Adult general medicine patients with ≥1 visit during the preceding year, stratified by 4 categories: African-American (N= 1,400), English-speaking Latino (N= 894), Spanish-speaking Latino (N= 965), and non-Latino white (N= 1,400). MEASUREMENTS AND RESULTS: Ethnically tailored initial letters referred to shortages of African-American (or Latino) physicians and the need to learn about the experiences of African-American (or Latino) patients communicating with physicians. Of 2,482 patients contacted, eligible, and able to participate (identified eligibles), 69.9% completed the survey. Thirty-nine percent of the sampling frame was unable to be contacted, with losses higher among non-Latino whites (46.5%) and African Americans (44.2%) than among English-speaking (32.3%) and Spanish-speaking Latinos (25.1%). For identified eligibles, response rates were highest among Spanish-speaking Latinos (75.2%), lowest for non-Latino whites (66.4%), and intermediate for African Americans (69.7%) and English-speaking Latinos (68.1%). There were no differences in overall response rates between patients receiving ethnically tailored letters (72.2%) and those receiving general letters (70.0%). CONCLUSIONS: Household contact and individual response rates differed by ethnic-language group, highlighting the importance of tracking losses by stage and subpopulation. Careful attention to recruitment yielded acceptable response rates among all groups.